Desarrollo de un simulador bajo el entorno de matlab para un circuito de molienda y clasificación directa más común en los procesos de conminución de minerales. - Briceño Arangurí, Edier Giancarlo (2015)
In this paper a simulation using MATLAB for grinding circuit and direct classification, for which the material balance equations arising in the circuit is developed, considering that there are three nodes necessarily the circuit is divided into three subsystems, the first subsystem in the circuit, (S1) is formed by the hydrocyclone and the the second subsystem (S2) is formed by joining two streams fresh feed and the hydrocyclone underflow, the third subsystem (S3) is formed by the mill. Because the feed to the mill depends on the discharge of the hydrocyclone feed to the hydrocyclone and depends on the mill discharge therefore is solved iteratively by the method of fixed point, the variable which is iterated is circulating load, for start the simulation must enter the dimensions of the equipment with operating conditions plus an initial value for the circulating load, once achieved convergence mass balance circuit, the particle size distribution is obtained in each currents, the hydrocyclone efficiency and energy consumption in the mill. The validation of the developed simulator was performed using literature data so it is concluded that lets us know particle sizes, the material balance circuit, operating parameters of the equipment, energy consumption and apply it to optimization which makes it useful tool for the engineer in charge of processes involving stages of grinding and subsequent classification.